Adapting the Bebras Challenge into an Educational Game for Learning Computational Thinking and Assessing Its Usability - Sukirman, Sukirman; Yuliana, Irma; Ramadhan, Fakhri Aulia Wildan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Computational thinking (CT) has become an essential component of secondary education, with several countries, including Indonesia, integrating CT tasks, such as those from the Bebras Challenge, into the national informatics curriculum. However, these tasks are often presented in static and text-based formats, limiting their potential to engage learners in interactive and meaningful ways. This study aimed to develop and evaluate the usability of an educational game adapted from a Bebras Challenge problem, "Magic Potion". It was designed to be aligned with the Grade 8 Informatics curriculum in Indonesia. The game engages students in CT through experimentation-based gameplay, where players mix potions to observe the effects on digital flowers and deduce which potion contains water. Using a Design and Development Research (DDR) framework, the game was tested with 55 junior high school students, who then completed the System Usability Scale (SUS) and open-ended feedback questions. The results yielded a mean SUS score of 75.3, indicating good usability. Qualitative feedback highlighted the game’s visual appeal, interactivity, and cognitive engagement. These findings suggest that curriculum-based CT tasks can be effectively transformed into engaging game-based learning tools, offering accessible entry points for introducing CT in formal educational contexts.